Study on Microwave Dielectric Materials an Adjustable Temperature Drift Coefficient and a High Dielectric Constant - Yuan-Bin Chen; Yu Fan; Shiuan-Ho Chang; Shaobing Shen (Ceramics)
This paper reports the dielectric characterizations of (Ca0.95Sr0.05)(Ti1−xSnx)O3 ceramics prepared using a solid-state reaction method with various x values. X-ray diffraction spectroscopy analyses showed that the crystal structure of these pure samples was orthorhombic perovskite. With increasing Sn4+ content, the lattice constant and unit cell volume increased, while the dielectric constant decreased because of the ionic polarizability decreasing. Moreover, a maximum Q × f value of 5242 (GHz), a dielectric constant (εr) of 91.23, and a temperature coefficient (τf) of +810 ppm/°C were achieved for samples sintered at 1350 °C for 4 h. The microwave dielectric characterization was found to be strongly correlated with the sintering temperature, and the best performance was achieved for the sample sintered at 1350 °C. (Ca0.95Sr0.05)(Ti1−xSnx)O3 possesses a promising potential to be a τf compensator for a near-zero τf dielectric ceramic applied in wireless communication systems.